Femtomolar hydrogen sulfide detection via hybrid small-molecule nano-arrays - Xing Xing; Luyan Wu; Yuchen Zhang; Jiahao Pan; Yusuke Ishigaki; Huaqing Xie; Takanori Suzuki; Deju Ye; Jianhua Zhang; Weihua Zhang; Zhenda Lu (Nature Communications)
Abstract Early disease diagnosis hinges on the sensitive detection of signaling molecules. Among these, hydrogen sulfide (H2S) has emerged as a critical player in cardiovascular and nervous system signaling. On-chip immunoassays, particularly nanoarray-based interfacial detection, offer promising avenues for ultra-sensitive analysis due to their confined reaction volumes and precise signal localization. Beyond the DNA or protein biomolecules array, this work presents a promising hybrid small molecule nano-array for H2S detection, using the power of dual molecules: a dye for fluorescence emission and a quencher with specific H2S reactivity. Upon H2S interaction, the quenched fluorescence reignites, creating an easily detectable array of bright spots. The molecule nano-array sensor shows exceptional responses to H2S over 8 magnitudes of dynamic range from 1 fM to 0.1 μM, with a remarkable detection limit of 1 fM, just using a 10 μL solution. This H2S detection method has the potential to significantly improve bioassay platforms, and the hybrid small-molecule nano-arrays we developed could be a valuable tool for advancing signaling molecule detection.